Development of Communication Strategy of UPT Region VI Bapenda City of Medan in Improving Taxpayer Compliance - Lubis, Gusti Erli Anggi; Zaniarti (International Humanity Advance, Business & Sciences, 2025)
In Indonesia, taxpayer compliance is one of the important indicators in achieving fiscal goals and sustainable development. However, in practice, the level of public compliance with tax payments is still a significant challenge, especially in the Medan City area. This study adopts a qualitative approach, where researchers apply descriptive methods to describe and explain in detail the development of a communication strategy for UPT Region VI Bapenda Medan City in an effort to improve taxpayer compliance. The results of this study indicate that to achieve these goals, it is necessary to develop a planned communication strategy, including identifying communication targets, choosing the right media, and composing clear and persuasive messages. Developing an effective communication strategy is a crucial step in encouraging taxpayer compliance and creating a society that is more aware of their tax responsibilities.